HLA DRB1, DQB1 and insulin promoter VNTR polymorphisms: interactions and the association with adult-onset diabetes mellitus in Czech patients - Daňková, Pavlína; Novota, Peter; Černá, Marie; Kološtová, Katarína; Nováková, Dana; Kučera, Petr; Novák, Jan; Anděl, Michal; Weber, Pavel; Žďárský, Emanuel (International journal of immunogenetics, 2008)
Both the human leucocyte antigen (HLA) DRB1 and the HLA DQB1 gene loci play a role in the development and progression of autoimmune diabetes mellitus (T1DM). Similarly, the insulin promoter variable number tandem repeats (INS-VNTR) polymorphism is also involved in the pathogenesis of diabetes mellitus (DM). We studied the association between each of these polymorphisms and DM diagnosed in patients older than age 35 years. Furthermore, we analysed possible interactions between HLA DRB1/DQB1 and INS-VNTR polymorphisms. Based on C-peptide and GADA levels we were able to distinguish three types of diabetes: T1DM, latent autoimmune diabetes in adults (LADA) and T2DM. INS-VNTR was genotyped indirectly by typing INS-23HphI A/T polymorphism. The genotype and allele frequencies of INS-23HphI did not differ between each of the diabetic groups and group of healthy subjects. We did, however, observe an association between the INS-23HphI alleles, genotypes and C-peptide secretion in all diabetic patients: A allele frequency was 86.2% in the C-peptide-negative group vs. 65.4% in the C-peptide-positive group (P(corr.) < 0.005); AA genotype was found to be 72.4% in the C-peptide-negative group vs. 42.6% in the C-peptide-positive groups (P(corr.) < 0.01). The HLA genotyping revealed a significantly higher frequency of HLA DRB1*03 allele in both T1DM and LADA groups when compared to healthy subjects: T1DM (25.7%) vs. control group (10.15%), odds ratio (OR) = 3.06, P < 0.05; LADA (27.6%) vs. control (10.15%), OR = 3.37, P < 0.01. The simultaneous presence of both HLA DRB1*04 and INS-23HphI AA genotype was detected in 37.5% of the T1DM group compared to only 9.2% of the healthy individuals group (OR = 5.9, P(corr.) < 0.007). We summarize that in the Central Bohemian population of the Czech Republic, the INS-23HphI A allele appears to be associated with a decrease in pancreatic beta cell secretory activity. HLA genotyping points to at least a partial difference in mechanism, which leads to T1DM and LADA development as well as a more diverse genetic predisposition in juvenile- and adult-onset diabetes. The simultaneous effect of HLA and INS-VNTR alleles/genotypes predispose individuals to an increased risk of diabetes development.
Keywords: věk při počátku nemoci; Age of Onset; HLA-DR antigeny; lidé; Middle Aged; Adult; Risk Factors; Female; inzulin; HLA-DR Antigens; HLA-DQ antigeny; Gene Frequency; Promoter Regions, Genetic; diabetes mellitus 1. typu; Humans; Polymorphism, Genetic; frekvence genu; Česká republika; Diabetes Mellitus, Type 1; lidé středního věku; mužské pohlaví; genetická predispozice k nemoci; minisatelitní repetice; Czech Republic; ženské pohlaví; Alleles; HLA-DQ Antigens; Male; Minisatellite Repeats; alely; Genetic Predisposition to Disease; dospělí; Insulin